2008
DOI: 10.1103/physreve.77.056301
|View full text |Cite
|
Sign up to set email alerts
|

Lagrangian particle statistics in turbulent flows from a simple vortex model

Abstract: The statistics of Lagrangian particles in turbulent flows is considered in the framework of a simple vortex model. Here, the turbulent velocity field is represented by a temporal sequence of Burgers vortices of different circulation, strain, and orientation. Based on suitable assumptions about the vortices' statistical properties, the statistics of the velocity increments is derived. In particular, the origin and nature of small-scale intermittency in this model is investigated both numerically and analyticall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…In addition to that, for the components’ increments were anti-correlated, which, as shown by Wilczek et al. (2008), can result from trajectories rotation around vortex filaments’ cores; this too supports the picture of vortex trapping. Thus, figure 3( b ) supports the notion that small-scale Lagrangian intermittency in the canopy flow is related to the encounter of trajectories with sparse and intense vortex filaments, similar to the HIT case.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…In addition to that, for the components’ increments were anti-correlated, which, as shown by Wilczek et al. (2008), can result from trajectories rotation around vortex filaments’ cores; this too supports the picture of vortex trapping. Thus, figure 3( b ) supports the notion that small-scale Lagrangian intermittency in the canopy flow is related to the encounter of trajectories with sparse and intense vortex filaments, similar to the HIT case.…”
Section: Resultssupporting
confidence: 66%
“…Let us briefly consider dynamical scenarios for small-scale Lagrangian intermittency. Results from HIT DNS by Biferale et al (2005), Bec et al (2006) and Bentkamp et al (2019) suggested that small-scale intermittency is a result of encounters between particles and intense vortex filaments; indeed, Wilczek, Jenko & Friedrich (2008) showed that the characteristic transition of the increments' p.d.f.s can be captured by a heuristic flow model of superimposed constitutive vortices. Similarly, Liberzon et al (2012) showed that acceleration-vorticity-strain alignment in a quasi-homogeneous flow is associated with intense energy flux.…”
Section: Lagrangian Velocity Increments and Small-scale Intermittencymentioning
confidence: 96%
“…Specific turbulent flow structures, vortices [e.g. [10][11][12] and straining stagnation points [13,14], have been identified as likely important to the statistics of those motions, and both of these have been employed as fundamental dynamical components in models of Lagrangian velocity increments [15][16][17] and pair dispersion [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ensembles of such model vortices have been shown to provide a reasonable approximation, and hence a testing ground, for realistic turbulent flows [35]. This has motivated earlier authors to use such models for understanding problems of Lagrangian turbulence [36] as well as turbulent transport of heavy inertial particles [37,38]. In a similar spirit, we analyze the relative motion of droplets suspended in and around a Burgers vortex, in order to gain insight into the enhancement of droplet collisions by intense vortical structures in turbulent flows.…”
Section: Introductionmentioning
confidence: 99%